Enhanced He’s frequency-amplitude formulation for nonlinear oscillators - Alex Elías-Zúñiga; Luis Manuel Palacios-Pineda; Isaac H. Jiménez-Cedeño; Oscar Martínez-Romero; Daniel Olvera-Trejo (Results in Physics, 2020)
In this article, a trial residual Jacobi elliptic weighted function is introduced to obtain the frequency-amplitude expression of nonlinear oscillators using He’s formulation. Simulation results show an improvement in the accuracy of the frequency values when compare to numerical integration simulations.